Investigating the Interaction between the Neonatal Fc Receptor and Monoclonal Antibody Variants by Hydrogen/Deuterium Exchange Mass Spectrometry - Jensen, Pernille Foged (Mol Cell Proteomics, 2015)
The recycling of immunoglobulins by the neonatal Fc receptor (FcRn) is of crucial importance in the maintenance of antibody levels in plasma and is responsible for the long half-lives of endogenous and recombinant monoclonal antibodies. From a therapeutic point of view there is great interest in understanding and modulating the IgG–FcRn interaction to optimize antibody pharmacokinetics and ultimately improve efficacy and safety. Here we studied the interaction between a full-length human IgG(1) and human FcRn via hydrogen/deuterium exchange mass spectrometry and targeted electron transfer dissociation to map sites perturbed by binding on both partners of the IgG–FcRn complex. Several regions in the antibody Fc region and the FcRn were protected from exchange upon complex formation, in good agreement with previous crystallographic studies of FcRn in complex with the Fc fragment. Interestingly, we found that several regions in the IgG Fab region also showed reduced deuterium uptake. Our findings indicate the presence of hitherto unknown FcRn interaction sites in the Fab region or a possible conformational link between the IgG Fc and Fab regions upon FcRn binding. Further, we investigated the role of IgG glycosylation in the conformational response of the IgG–FcRn interaction. Removal of antibody glycans increased the flexibility of the FcRn binding site in the Fc region. Consequently, FcRn binding did not induce a similar conformational stabilization of deglycosylated IgG as observed for the wild-type glycosylated IgG. Our results provide new molecular insight into the IgG–FcRn interaction and illustrate the capability of hydrogen/deuterium exchange mass spectrometry to advance structural proteomics by providing detailed information on the conformation and dynamics of large protein complexes in solution.